(Eco)Ethical Issues in Organizations Including Healthcare Facilities - Myszograj, Martyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Ethics issues are present in the daily life of every human being. This paper presents an overview of difficult, yet everyday ethics dilemmas, and general rules and tools helping in making ethical choices. These tools are: distinguishing facts from values, reasoning from principles, defining terms and clarifying concepts, comparing cases, thought experiments, logic, and recognizing and avoiding errors in reasoning.
Keywords: ethics; medical ethics; healthcare; ecoethics; etyka; etyka lekarska; ochrona zdrowia; ekoetyka